2009
DOI: 10.1163/156854109x446980
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal change in susceptibility of Pinus densiflora to Bursaphelenchus xylophilus infection, determined from the number of nematodes passing through branch sections

Abstract: Pine wilt disease by Bursaphelenchus xylophilus has been causing devastating damage to Pinus densiflora and P. thunbergii forests in Japan. Reforestation using resistant trees is one of the most effective control measures. In this study we examined the seasonal change in the number of nematodes passing through 5 cm long P. densiflora branch sections during 24 h, to determine the season of greatest susceptibility when resistant candidates can be identified easily. We inoculated 200 nematodes of each of four B. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Panesar and Sutherland (1989) performed several inoculation tests under the same climatic conditions but different inoculation months, and reported higher seedling mortality rates for March inoculations. A seasonal pattern was even observed for B. xylophilus multiplication in P. densiflora and P. pinaster branch sections (Matsunaga and Togashi 2009;Menéndez-Gutiérrez et al 2017c) due to the environmental conditions of the trees prior to the experiment.…”
Section: Discussionmentioning
confidence: 96%
“…Panesar and Sutherland (1989) performed several inoculation tests under the same climatic conditions but different inoculation months, and reported higher seedling mortality rates for March inoculations. A seasonal pattern was even observed for B. xylophilus multiplication in P. densiflora and P. pinaster branch sections (Matsunaga and Togashi 2009;Menéndez-Gutiérrez et al 2017c) due to the environmental conditions of the trees prior to the experiment.…”
Section: Discussionmentioning
confidence: 96%
“…The reason for the significant decrease summer mean NDVI of Pinus tabulaeformis forest and Pinus densiflora forest is probably insect disease, such as pine wilt disease. It is reported that the month of greatest susceptibility to pine wilt disease for Pinus densiflora is August in Japan (Matsunaga and Togashi 2009).…”
Section: Seasonal Variation Of Mean Seasonal Ndvimentioning
confidence: 99%
“…Such beetles feed on the healthy bark of pine twigs, and the nematodes enter the tree bodies through the feeding wounds (Mamiya and Enda 1972). Some inoculated nematodes disperse at a great rate of over 1 m per day in intact trees (Kuroda and Ito 1992) and at a rate of more than 5 cm per day in excised pine seedling stems and branches (Matsunaga and Togashi 2009;Oku et al 1989;Son et al 2010;Togashi and Matsunaga 2003). The beetles lay the eggs under the bark of pine trees recently killed by B. xylophilus infection (Mamiya 1983).…”
Section: Introductionmentioning
confidence: 99%